Assessing war : the challenge of measuring success and failure - Blanken, Leo J. (Leo James); Rothstein, Hy S.; Lepore, Jason J. (Georgetown University Press, 2015)
Are we winning? Combatants often find themselves asking this question, especially during today's protracted asymmetrical conflicts where victory and defeat are not clear or easy to measure. Also, too often politics or wishful thinking take the place of objective assessment. Assessing War explores how the trajectory of war has been analyzed in conflicts throughout American history. The book brings together military historians, political scientists, and military officers to examine wartime assessment in theory, in practice through historical and contemporary cases, and through alternative dimensions of assessment such as justice and proportionality, the war of ideas, and economics. The cases start with the Seven Year's War and cover all major US conflicts through the war in Afghanistan. There are also unique examinations of how Al Qaeda has assessed its war on the United States and how assessment might be conducted in cyber war. Wartime assessment is critical because forming an accurate picture is essential to developing the right strategy. This book concludes with advice for practitioners about best approaches, though it also offers sobering conclusions about the difficulty of assessing war objectively and without politicization or self delusion.